In situ regeneration of nasal septal defects using acellular cartilage enhanced with platelet-derived growth factor - Huber, Lena; Gvaramia, David; Kern, Johann; Jakob, Yvonne; Zöllner, Frank G.; Hirsch, Daniela; Breiter, Roman; Brenner, Rolf E.; Rotter, Nicole (Journal of tissue engineering, 2022)
Nasal septum defects can currently only be reconstructed using autologous cartilage grafts. In this study, we examine the reconstruction of septal cartilage defects in a rabbit model using porcine decellularized nasal septal cartilage (DNSC) functionalized with recombinant platelet-derived growth factor-BB (PDFG-BB). The supportive function of the transplanted DNSC was estimated by the degree of septum deviation and shrinkage using magnetic resonance imaging (MRI). The biocompatibility of the transplanted scaffolds was evaluated by histology according to international standards. A study group with an autologous septal transplant was used as a reference. In situ regeneration of cartilage defects was assessed by histological evaluation 4 and 16 weeks following DNSC transplantation. A study group with non-functionalized DNSC was introduced for estimation of the effects of PDFG-BB functionalization. DNSC scaffolds provided sufficient structural support to the nasal septum, with no significant shrinkage or septal deviations as evaluated by the MRI. Biocompatibility analysis after 4 weeks revealed an increased inflammatory reaction of the surrounding tissue in response to DNSC as compared to the autologous transplants. The inflammatory reaction was, however, significantly attenuated after 16 weeks in the PDGF-BB group whereas only a slight improvement of the biocompatibility score was observed in the untreated group. In situ regeneration of septal cartilage, as evidenced by the degradation of the DNSC matrix and production of neocartilage, was observed in both experimental groups after 16 weeks but was more pronounced in the PDFG-BB group. Overall, DNSC provided structural support to the nasal septum and stimulated in situ regeneration of the cartilage tissue. Furthermore, PDFG-BB augmented the regenerative potential of DNSC and enhanced the healing process, as demonstrated by reduced inflammation after 16 weeks.
Gesehen am 26.09.2023